A method for preparing magnetic powder samples of steel metallurgical solid waste transmission electron microscope
In the preparation of transmission electron microscope magnetic powder sample, the mixing of finely ground magnetic powder with embedded resin and curing agent and a two-step curing method are used, combined with ultra-thin slice and diamond tool technology, the problem of uneven sample settlement and difficulty in slices is solved, and high-resolution observation and electron diffraction analysis are achieved.
Patent Information
- Application Number
- CN202210637822.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-07
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-06-07
AI Technical Summary
The prior art is difficult to observe and analyze magnetic powder samples in steel metallurgy solid waste with high resolution in transmission electron microscopy and electron diffraction. Especially due to the large hardness and particle size of the magnetic powder, the samples are unevenly settled in the resin and difficult to slice.
A preparation method is adopted to perform two-step curing and ultra-thin slices by grinding the magnetic powder and mixing it with embedded resin and curing agent in a specific proportion. The high resolution and conductivity of the sample are ensured using diamond cutters and ultra-thin carbon film mesh.
High-resolution observation and electron diffraction analysis of solid waste magnetic powder samples of steel metallurgy have been realized, solving the problems of uneven settlement of samples in the resin and difficulty in slicing, and improving the slice quality and analysis effect.
Smart Images

Figure CN115389282B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano material measurement and relates to a method for preparing a transmission electron microscope magnetic powder sample. Background Art
[0002] Iron and steel metallurgical solid waste refers to some dust and slag produced in the whole process of steel production. These solid wastes contain valuable metal elements such as iron, zinc, chromium, and nickel. In order to better study and utilize metallurgical solid waste, its microscopic morphology and microstructure must be clearly characterized at the microscopic scale. Transmission electron microscopy can obtain high-resolution lattice images and electron diffraction patterns of materials at the nanoscale, but in the process of analyzing magnetic samples, magnetic powder may be adsorbed on the pole shoe of the objective magnetic lens, which can easily cause damage to the pole shoe and seriously affect the imaging quality.
[0003] To prevent magnetic powder particles from being adsorbed on the pole piece, the commonly used treatment methods currently include: 1) applying an external magnetic field before placing it in a transmission electron microscope to remove magnetic powder that is not firmly attached to the carbon film on the grid; however, this method may cause all the magnetic powder to be absorbed by the external magnetic field; 2) using a double network to sandwich the magnetic powder between two layers of carbon film, and using the strength of the carbon film to protect the magnetic powder from being adsorbed by the pole piece; however, there is a height difference between the two layers of carbon film, resulting in problems such as being unable to focus at the same time; 3) using a demagnetizer to weaken or even eliminate the magnetism of the magnetic powder; but it is still possible to be magnetized again by the magnetic field of the objective lens; 4) using a chemical reaction to convert the magnetic material in the magnetic powder into a non-magnetic material; however, the change in the phase of the magnetic powder will also cause trouble for the analysis of the sample; 5) embedding the magnetic powder sample with resin, solidifying it into a round rod shape, and then slicing and ion thinning; however, the hardness difference between the resin and the powder particles is large, and the ion beam will more easily penetrate the resin, so that the final thinning result is that the powder particles cannot be reduced to a sufficient thinness, and high-resolution observation and electron diffraction analysis cannot be performed, making the microstructural analysis of the magnetic powder sample in the transmission electron microscope extremely difficult. For example, patent CN112786270A discloses a method for preparing a transmission electron microscope sample of magnetic powder particles, wherein the magnetic powder particles are embedded in a transmission electron microscope sample support net, fixed with resin, thin film materials are arranged on the upper and lower layers, and compacted with a clamp to make the resin evenly distributed, completely wrap the support net and the magnetic powder, exhaust the existing air, heat and cool after heat preservation, take out the support net, and finally ion thinning to prepare a thin area. Although this method can ensure the uniform thickness of the support net, it also has the consequence that the ion beam is more likely to penetrate the resin, and the magnetic powder particles cannot be effectively thinned. Therefore, the prepared sample is also difficult to perform high-resolution observation and electron diffraction analysis. The magnetic powder contained in metallurgical solid waste is mostly ferroferric oxide particles with an inverse spinel structure, with a particle size of more than 6um and a Mohs hardness of 6.0-6.5. Therefore, the above-mentioned sample preparation methods cannot well characterize the microstructure and micromorphology of metallurgical solid waste.
[0004] In addition, ultrathin sectioning is a method for preparing biological samples for transmission electron microscopy, and can also be used to cut soft inorganic materials. However, for magnetic powder samples containing ferroferric oxide with larger particle size and hardness, such as iron and steel metallurgical solid waste, there are problems such as difficulty in sample preparation; there is no report on the technical solution of using ultrathin sectioning to prepare iron and steel metallurgical solid waste-based transmission electron microscopy magnetic powder samples for high-resolution observation and electron microscopic analysis. Summary of the invention
[0005] The main purpose of the present invention is to provide a method for preparing a transmission electron microscopy magnetic powder sample of solid waste from steel metallurgy in view of the problems and shortcomings existing in the microstructure analysis process of existing transmission electron microscopy magnetic powder samples, and in view of the characteristics of magnetic powders containing hard magnetic particles such as ferroferric oxide, such as large particle size and hardness, so as to achieve high-resolution observation and electron diffraction analysis of transmission electron microscopy magnetic powder samples of solid waste from steel metallurgy.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing a transmission electron microscope magnetic powder sample, using magnetic powder and an embedding agent as main raw materials, wherein the embedding agent includes an embedding resin and an embedding curing agent; the specific preparation steps include the following:
[0008] 1) Grind the magnetic powder (milling, etc.), sieve, and dry;
[0009] 2) mixing the dried magnetic powder and the embedding resin in proportion, and then stirring to obtain a magnetic powder / resin; then adding an embedding curing agent in proportion, and stirring to obtain a magnetic powder / embedding agent mixture;
[0010] 3) injecting the obtained magnetic powder / embedding agent mixture into an embedding tube, and then curing it at 60-70°C; during this process, rotating the embedding tube up and down at intervals to interchange the bottom and top;
[0011] 4) performing secondary solidification on the product obtained in step 3), taking out the embedding tube, and cooling it naturally to room temperature to obtain an embedding block;
[0012] 5) Slice the embedded block obtained, and scoop out the slices with an ultra-thin carbon film support net; thus, the transmission electron microscopy magnetic powder sample is obtained.
[0013] In the above scheme, the magnetic powder is iron and steel metallurgical solid waste, which contains magnetic particles such as ferroferric oxide, elemental iron or iron-nickel alloy with a Mohs hardness of 5.5 to 9.0 and a particle size of less than 8.0 μm.
[0014] Furthermore, the hardness of the ferroferric oxide magnetic particles is 6.0-6.5; the Mohs hardness of the elemental iron or iron-nickel alloy magnetic particles is less than 9.0.
[0015] In the above solution, the content of the magnetic particles is greater than 1 wt %.
[0016] In the above scheme, the iron and steel metallurgical solid waste can be selected from steel slag, blast furnace gas ash, gas mud, sintering ash, ironmaking bag ash, etc.
[0017] In the above scheme, the sieving step in step 1) is to sieve through a 2000 mesh sieve.
[0018] In the above scheme, the drying temperature in step 1) is 105-110° C. and the drying time is 2-2.5 hours.
[0019] In the above scheme, the embedding agent includes an embedding agent resin and an embedding curing agent; specifically, Epon 812 embedding agent kit, SPI-Pon812 embedding agent kit, Eponate12 embedding agent kit, etc. can be selected, wherein the embedding agent resin is Epon812 resin, SPI-Pon812 resin or Eponate12 resin respectively; the curing agent includes DDSA hardener, MNA hardener and DMP-30 accelerator.
[0020] In the above scheme, the mass ratio of the dried magnetic powder to the embedding resin is (0.15-0.25):1; the volume ratio of the embedding resin, DDSA hardener, MNA hardener, and DMP-30 accelerator is (30-50):(10-18):(26.6-43):1.
[0021] In the above scheme, the stirring rate adopted in the stirring treatment step in step 2) is 50-60 r / min, and the stirring time is 2-2.5 h.
[0022] Preferably, in step 3), the vertically placed embedding tube is rotated 180° every 15-30 minutes to allow the materials at the bottom and top of the tube to be slowly exchanged up and down.
[0023] In the above scheme, the curing temperature used in the secondary curing step is the same as that in step 3), and the curing time is 36 to 38 hours.
[0024] In the above scheme, an ultrathin slicer is used to slice the embedded block, the cutter used is a diamond knife, and the slice thickness is 60 to 100 nm.
[0025] The method is applicable to the preparation of various transmission electron microscope magnetic powder samples; in particular, it is applicable to high-hardness magnetic powders with a Mohs hardness ranging from 5.5 to 9.0.
[0026] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1) The present invention adjusts the ratio between magnetic powder and embedding resin and between embedding resin and curing agent, adds resin and curing agent to "hard, large-particle-size" magnetic powder in steps, and combines curing methods such as two-step curing to effectively solve the problem of sedimentation and uneven dispersion of powder samples in the resin during the curing process, thereby avoiding problems such as difficulty or failure in slicing caused by sedimentation and aggregation of powder samples and difficulty in cutting hard, large-particle-size magnetic particles;
[0029] 2) Using a diamond cutter for slicing can effectively ensure the success rate of slicing and ensure that the solidified magnetic powder particles are cut into thin slices with a thickness of no more than 100nm;
[0030] 3) Using ultra-thin carbon film as a mesh carrier can make the obtained slices adhere better to the carbon film, increase the conductivity of the sample, reduce the background noise of the image, and further improve the quality of high-resolution images;
[0031] 4) The slice quality of the transmission electron microscope magnetic powder sample obtained by the present invention is high, especially for magnetic powder particles with a particle size of 5.0um or more, its high-resolution image and electron diffraction pattern can also be directly photographed; and the sample preparation method involved is relatively simple and easy to operate, which is suitable for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a transmission electron microscope image of a slice of a magnetic powder-containing sample obtained in Example 1, with a magnification of 2600×;
[0033] Figure 2 for Figure 1 High-resolution image at the white circle, magnification 1.05M×;
[0034] Figure 3 for Figure 1 Electron diffraction pattern captured at the white circle;
[0035] Figure 4 For Figure 1 The high-resolution image in the white dotted frame in the middle has a magnification of 1.05M×;
[0036] Figure 5 For Figure 1 The electron diffraction pattern captured in the white dotted frame;
[0037] Figure 6 This is a transmission electron microscope image of a slice of the magnetic powder-containing sample obtained in Comparative Example 1, with a magnification of 2600×. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0039] In the following examples, the embedding medium set used is the Epon 812 embedding medium set provided by Beijing Xinxing Bairui Technology Co., Ltd., which consists of SPI-Epon 812 resin, DDSA hardener, MNA hardener and DMP-30.
[0040] The magnetic powder used was collected from metallurgical solid waste (blast furnace gas mud) produced by Taiyuan Iron and Steel Group Corporation. Its iron content (in terms of Fe2O3) was 59.60% and its volume magnetic susceptibility was 6.16×10 -4 Oe (the content of ferrosoferric oxide is above 1wt%); and the following transmission electron microscopy analysis results show that it contains ferrosoferric oxide particles above 5.0um.
[0041] The ultra-thin carbon film used is provided by Beijing Xinxing Bairui Technology Co., Ltd., and its carbon film thickness is 3 to 5nm.
[0042] Example 1
[0043] A method for preparing a transmission electron microscope magnetic powder sample comprises the following steps:
[0044] 1) Grind the magnetic powder with an agate mortar and pass it through a 2000 mesh sieve; then dry it at 105°C for 2h;
[0045] 2) Mix the dried magnetic powder with SPI-pon 812 resin (the mass ratio of the magnetic powder to the SPI-pon 812 resin is 0.15:1), and stir with a stirrer for 2 hours to make them evenly mixed (stirring rate 50r / min); then add a curing agent, stir for 2 hours to make them evenly mixed, and obtain a magnetic powder / embedding agent mixture; wherein the volume ratio of the embedding resin, DDSA hardener, MNA hardener, and DMP-30 accelerator is 40:13.33:33.33:1;
[0046] 3) The obtained magnetic powder / embedding agent mixture was injected into an embedding tube with a diameter of 1 cm, and then the embedding tube was placed in an oven at 60°C for curing for 12 hours. During this period, the embedding tube was rotated 180° every half an hour to interchange the upper and lower positions of the bottom and top of the tube to prevent the magnetic powder from settling and aggregating in the resin;
[0047] 4) Continue curing for 36 hours (60°C), take out the embedded tube, and place it in a desiccator to cool naturally to room temperature;
[0048] 5) Use an ultrathin slicer to slice the cooled embedded block. The cutter used for slicing is a diamond knife with a slice thickness of 100 nm.
[0049] 6) Pick up the slices with a copper grid for later use, thus obtaining the transmission electron microscope magnetic powder sample; wherein the copper grid is an ultra-thin carbon film to enhance the adhesion and conductivity of the slices and reduce the background noise of the image.
[0050] The TEM magnetic powder prepared in this example was placed in the TEM, the axis of the TEM was adjusted, and the microscopic morphology of the sample was photographed at a low magnification (2600×). Figure 1 As shown, it can be seen that small particles of different sizes are obviously attached to the obtained slices.
[0051] choose Figure 1 A small particle with a particle size of less than 0.8um (white circle) was observed in the image. Its high-resolution image was observed under high magnification, as shown in the figure below. Figure 2 As shown in the figure, the lattice fringes of the small particles can be clearly observed, indicating that the small particles are well crystalline. Switch the working mode of the electron microscope from the image mode to the diffraction mode and take a picture of the electron diffraction pattern of the small particles, as shown in the figure below. Figure 3 As shown, analysis shows that the particles are Fe3O4 crystals, and the corresponding PDF card number is #76-0956.
[0052] choose Figure 1 A large particle with a particle size of more than 5.0 μm (in the white dotted frame) is observed in the figure. Its high-resolution image is observed under high magnification, as shown in the figure below. Figure 4 As shown in the figure, the lattice fringes of the large particles can be clearly observed, indicating that the large particles are also well crystalline. Switch the electron microscope working mode from image mode to diffraction mode and take a picture of the electron diffraction pattern of the large particles, as shown in the figure below. Figure 5 As shown, analysis shows that this particle is also Fe3O4 crystal, and the corresponding PDF card number is also #76-0956.
[0053] The above results indicate that the transmission electron microscopy analysis of the magnetic powder sample obtained by the above method of the present invention can be used to observe high-resolution images and electron diffraction patterns of magnetic powder particles with a particle size of 5.0 um or more, thereby solving the difficult problem of analyzing the microstructure of magnetic powder samples (especially large-size hard magnetic particles) using transmission electron microscopy.
[0054] Example 2
[0055] A method for preparing a transmission electron microscope magnetic powder sample comprises the following steps:
[0056] 1) Grind the magnetic powder with an agate mortar and pass it through a 2000 mesh sieve; then dry it at 105°C for 2h;
[0057] 2) Mix the dried magnetic powder with SPI-pon 812 resin (the mass ratio of the magnetic powder to the SPI-pon 812 resin is 0.25:1), and stir with a stirrer for 2 hours to make them evenly mixed (stirring rate is 60r / min); then add a curing agent and stir for 2 hours to make them evenly mixed to obtain a magnetic powder / embedding agent mixture; wherein the volume ratio of the embedding resin, DDSA hardener, MNA hardener, and DMP-30 accelerator is 45:15:40:1;
[0058] 3) The obtained magnetic powder / embedding agent mixture was injected into an embedding tube with a diameter of 1 cm, and then the embedding tube was placed in an oven at 60°C for curing for 12 hours. During this period, the embedding tube was rotated 180° every half an hour to interchange the upper and lower positions of the bottom and top of the tube to prevent the magnetic powder from settling and aggregating in the resin;
[0059] 4) Continue curing for 36 hours (60°C), take out the embedded tube, and place it in a desiccator to cool naturally to room temperature;
[0060] 5) Use an ultrathin slicer to slice the cooled embedded block. The cutter used for slicing is a diamond knife with a slice thickness of 100 nm.
[0061] 6) Pick up the slices with a copper grid for later use, thus obtaining the transmission electron microscope magnetic powder sample; wherein the copper grid is an ultra-thin carbon film to enhance the adhesion and conductivity of the slices and reduce the background noise of the image.
[0062] Example 3
[0063] A method for preparing a transmission electron microscope magnetic powder sample comprises the following steps:
[0064] 1) Grind the magnetic powder with an agate mortar and pass it through a 2000 mesh sieve; then dry it at 105°C for 2h;
[0065] 2) Mix the dried magnetic powder with SPI-pon 812 resin (the mass ratio of the magnetic powder to the SPI-pon 812 resin is 0.2:1), and stir with a stirrer for 2 hours to make them evenly mixed (stirring rate 60r / min); then add a curing agent and stir for 2 hours to make them evenly mixed to obtain a magnetic powder / embedding agent mixture; wherein the volume ratio of the embedding resin, DDSA hardener, MNA hardener, and DMP-30 accelerator is 33.33:12:35.83:1;
[0066] 3) The obtained magnetic powder / embedding agent mixture was injected into an embedding tube with a diameter of 1 cm, and then the embedding tube was placed in an oven at 60°C for curing for 12 hours. During this period, the embedding tube was rotated 180° every half an hour to interchange the upper and lower positions of the bottom and top of the tube to prevent the magnetic powder from settling and aggregating in the resin;
[0067] 4) Continue curing for 36 hours (60°C), take out the embedded tube, and place it in a desiccator to cool naturally to room temperature;
[0068] 5) Use an ultrathin slicer to slice the cooled embedded block. The cutter used for slicing is a diamond knife with a slice thickness of 100 nm.
[0069] 6) Use a copper grid to pick up the cut slices for later use; the copper grid is an ultra-thin carbon film to enhance the adhesion and conductivity of the slices and reduce the background noise of the image.
[0070] Comparative Example 1
[0071] A method for preparing a transmission electron microscope magnetic powder sample comprises the following steps:
[0072] 1) Grind the magnetic powder with an agate mortar and pass it through a 2000 mesh sieve; then dry it at 105°C for 2h;
[0073] 2) Mix the dried magnetic powder with SPI-pon 812 resin (the mass ratio of magnetic powder to SPI-pon 812 resin is 0.15:1), stir with a stirrer for 2 hours to make them evenly mixed, and the stirring rate is 50 rpm; then add a curing agent, stir for 2 hours to make them evenly mixed, and obtain a magnetic powder / embedding agent mixture; wherein, the volume ratio of embedding resin, DDSA hardener, MNA hardener, and DMP-30 accelerator is 22.5:10:22.5:1;
[0074] 3) The obtained magnetic powder / embedding agent mixture was injected into an embedding tube with a diameter of 1 cm, and the embedding tube was placed in an oven at 60°C for curing for 12 hours. During this period, the embedding tube was rotated 180° every half an hour to interchange the upper and lower positions of the bottom and top of the tube to prevent the magnetic powder from settling and aggregating in the resin;
[0075] 4) Continue curing for 36 hours (60°C), take out the embedded tube, and place it in a desiccator to cool naturally to room temperature;
[0076] 5) Use an ultrathin slicer to slice the cooled embedded block. The cutter used for slicing is a diamond knife with a slice thickness of 100 nm.
[0077] 6) Use a copper grid to pick up the cut slices for later use; the copper grid is an ultra-thin carbon film to enhance the adhesion and conductivity of the slices and reduce the background noise of the image.
[0078] The TEM magnetic powder prepared in this comparative example was placed in an electron microscope, the axis of the electron microscope was adjusted, and the microscopic morphology of the sample was photographed at a low magnification (magnification of 2600×). Figure 6As shown, it can be seen that the obtained slices are thick and uneven, and the attached magnetic particles are fewer and thicker, which is not conducive to the observation of high-resolution images.
[0079] Comparative Example 2
[0080] A method for preparing a transmission electron microscope magnetic powder sample comprises the following steps:
[0081] 1) Grind the magnetic powder with an agate mortar and pass it through a 2000 mesh sieve; then dry it at 105°C for 2h;
[0082] 2) Mix the dried magnetic powder with SPI-pon 812 resin and curing agent, and stir them with a stirrer for 2 hours to make them uniformly mixed (stirring rate 60r / min); wherein the mass ratio of magnetic powder to SPI-pon 812 resin is 0.25:1, and the volume ratio of embedding resin, DDSA hardener, MNA hardener, and DMP-30 accelerator is 45:15:40:1;
[0083] 3) The obtained magnetic powder / embedding agent mixture was injected into an embedding tube with a diameter of 1 cm, and then the embedding tube was placed in an oven at 60°C for curing for 48 hours;
[0084] 4) Take out the embedding tube and put it in a desiccator to cool naturally to room temperature;
[0085] It was found that the magnetic powder was not evenly dispersed in the resin, but gathered at the bottom of the resin, making it impossible to perform subsequent slicing work and sample preparation failed. It can be seen that it is impossible to prepare ultra-thin slice magnetic samples by directly mixing magnetic powder with resin and curing agent for 48 hours.
[0086] Comparative Example 3
[0087] A method for preparing a transmission electron microscope magnetic powder sample comprises the following steps:
[0088] 1) Grind the magnetic powder with an agate mortar and pass it through a 2000 mesh sieve; then dry it at 105°C for 2h;
[0089] 2) Mix the dried magnetic powder with SPI-pon 812 resin (the mass ratio of magnetic powder to SPI-pon 812 resin is 0.1:1), and stir with a stirrer for 2 hours to make them evenly mixed (stirring rate is 60 rpm); then add a curing agent and stir for 2 hours to make them evenly mixed to obtain a magnetic powder / embedding agent mixture; wherein the volume ratio of embedding resin, DDSA hardener, MNA hardener, and DMP-30 accelerator is 52:15:40:1;
[0090] 3) The obtained magnetic powder / embedding agent mixture was injected into an embedding tube with a diameter of 1 cm, and then the embedding tube was placed in an oven at 60°C for curing for 12 hours. During this period, the embedding tube was rotated 180° every half an hour to interchange the upper and lower positions of the bottom and top of the tube to prevent the magnetic powder from settling and aggregating in the resin;
[0091] 4) Continue curing for 36 hours (60°C), take out the embedded tube, and place it in a desiccator to cool naturally to room temperature;
[0092] 5) Use an ultrathin slicer to slice the cooled embedded block. The cutter used for slicing is a diamond knife with a slice thickness of 100 nm.
[0093] 6) Pick up the slices with a copper grid for later use, thus obtaining the transmission electron microscope magnetic powder sample; wherein the copper grid is an ultra-thin carbon film to enhance the adhesion and conductivity of the slices and reduce the background noise of the image.
[0094] The above method reduces the amount of magnetic powder and increases the amount of resin. The magnetic powder can be dispersed evenly in the resin. When cutting samples containing magnetic particles with a size less than 2um, ultra-thin slices less than 100nm thick can be obtained, but there are fewer particles in the slices, and sometimes no particles can be seen in the slices, which is not conducive to research; when cutting samples with magnetic particles with a size of more than 2um, the resin will slide, and the hard and large magnetic particles cannot be effectively cut, which will lead to problems such as slicing failure. It can be seen from this that: when reducing the amount of magnetic powder and increasing the amount of resin, the quality of the slices is difficult to guarantee, and in particular, large magnetic particles cannot be effectively sliced.
[0095] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing magnetic powder samples of iron and steel metallurgical solid waste for transmission electron microscopy, characterized in that: The raw materials include magnetic powder and embedding agent, wherein the embedding agent includes embedding resin and embedding curing agent; the specific preparation steps include the following: 1) Grind the magnetic powder, sieve and dry it; 2) Mixing the dried magnetic powder and embedding resin in proportion, and then stirring to obtain magnetic powder / resin; then adding embedding curing agent in proportion, and stirring to obtain magnetic powder / embedding agent mixture; 3) The obtained magnetic powder / embedding agent mixture is injected into the embedding tube, and then cured at 60-70°C. During this process, the embedding tube is rotated up and down at intervals to interchange the bottom and top; 4) performing secondary solidification on the product obtained in step 3), taking out the embedding tube, and cooling it naturally to room temperature to obtain an embedding block; 5) Slicing the embedded block obtained, and scooping the slices with an ultra-thin carbon film support net to obtain the transmission electron microscopy magnetic powder sample; The embedding agent is selected from Epon 812 embedding agent set, SPI-Pon812 embedding agent set or Eponate12 embedding agent set, wherein the embedding resin is Epon 812 resin, SPI-Pon812 resin or Eponate12 resin respectively; the curing agent includes DDSA hardener, MNA hardener and DMP-30 accelerator; The mass ratio of the dried magnetic powder to the embedding resin is (0.15-0.25):1; the volume ratio of the embedding resin, DDSA hardener, MNA hardener, and DMP-30 accelerator is (30-50):(10-18):(26.6-43):
1.
2. The preparation method according to claim 1, characterized in that: The magnetic powder is solid waste from iron and steel metallurgy, and contains ferroferric oxide, elemental iron or iron-nickel alloy magnetic particles with a Mohs hardness of 5.5-9.
0.
3. The preparation method according to claim 2, characterized in that: The content of the magnetic particles is greater than 1 wt %.
4. The preparation method according to claim 1, characterized in that: The stirring rate used in the stirring treatment step in step 2) is 50-60 r / min, and the stirring time is 2-2.5 h.
5. The preparation method according to claim 1, characterized in that: The primary curing time is 10 to 12 hours.
6. The preparation method according to claim 1, characterized in that: The curing temperature used in the secondary curing step is the same as that in step 3), and the curing time is 36 to 38 hours.
7. The preparation method according to claim 1, characterized in that: The embedded blocks were cut using an ultrathin slicer with a diamond knife and a slice thickness of 60-100 nm.
Citation Information
Patent Citations
Preparation method of magnetic powder particle transmission electron microscope sample
CN112786270A
Preparation method of scanning electron microscope section sample of micron-sized powder
CN111982948A
Method for preparing high-density powder particle transmission electron microscope sample through film support
CN113804707A